New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand - Schawaller, Wolfgang; Bigalk, Sonia (Zootaxa, 2020)
The tenebrionid genus Indenicmosoma Ardoin, 1964 (type species indochinensis Kaszab, 1940), subfamily Lagriinae, is distributed in Asia and Sub-Saharan Africa. Newly collected specimens from different Palaearctic and Oriental Asian regions are presented, among them also one species new to science from Thailand (Indenicmosoma paicum sp. nov.). New synonym: Indenicmosoma nathani Ardoin, 1964 (Indenicmosoma ardoini Kaszab, 1970 syn. nov.). All treated eight Asian species are figured, and a species key is compiled.